Comparison anterior minimally invasive oblique retroperitoneal approach and posterior transpedicular approach for debridement fusion in patients with lumbar vertebral osteomyelitis: A randomized controlled trial protocol. Issue 44 (30th October 2020) - Gao, Xiang; Wan, Shu; Lv, Jie; Cheng, Wei; Zhang, Yangbin
Abstract: Background: Pyogenic osteomyelitis of the spine usually occurs in patients over 55 years old with acute osteomyelitis. Surgical treatment and fixation can relieve pain, enhance spinal balance and nerve function, so that patients can walk as soon as possible. Different outcomes of surgical methods include anterior minimally invasive oblique retroperitoneal approach (ORA) and posterior transpedicular approach (PTA). While, there is no consensus on the best treatment for PVO. The goal of the protocol is to compare the clinical consequences between PTA and ORA for treating PVO. Method: The experiment is a single-center randomized clinical research. This experiment was admitted by the Ethics Committee of the People's Hospital of Dayi County (Approval number: 1002-084). In all, 50 patients with lumbar vertebral osteomyelitis (LVO) who prepares surgical treatment will be included in the study. We contain adult patients (aged over 18 years) who accept debridement and spinal stabilization with LVO. Cases are removed if there is previous hardware placement, cases who are not confirmed by microbiology, or severe renal and liver dysfunction. The primary outcomes are intraoperative blood loss, operative time, hospital stay, primary failure and recurrence, and bone fusion. The secondary outcomes are postoperative pain score and physical recovery. SPSS Sample Power version 3.0 (IBM, Armonk, NY, USA) is used for data analysis. Results: Table 1 will show the outcomes in both groups. Conclusion: This protocol may offer a reliable basis for the effectiveness of the two approaches in the treatment of PVO. Trial registration number: researchregistry6046